Cord Blood CD34+ Expansion Using Vitamin-C: An Epigenetic Regulator - Almoflehi, Sakhar (Université d'Ottawa / University of Ottawa, 2020)
Vitamin-C (Vit-C) has been shown to modulate hematopoietic stem cells and leukemia stem cell frequency in-vivo. Herein, Vit-C analogue, L-ascorbic acid 2-phosphate (AA2P), was investigated as a new potential HSC expansion agonist. Cord blood CD34+ cells were expanded in cultures with or without AA2P. AA2P induced a 2-fold increase in the expansion of stem and progenitor subsets including lymphoid-primed multi-potential progenitors (p<0.05, n=3) and functional colony forming progenitors. The functional properties of AA2P grafts was evaluated with a xenotransplant model. Superior platelet levels in the periphery (p<0.05) and human bone marrow engraftment (median 75% hCD45+ cells for AA2P Vs. 48% for PBS control at week-22, n=3, p<0.05) was detected in AA2P cohorts Vs. control. In summary, my results demonstrate that AA2P is a new stem and progenitor expansion agonist with AA2P-expanded stem and progenitor cells capable of increased engraftment and higher platelet recovery. These findings may aid to overcome cord blood limitations; thereby, improving clinical relevance.
Keywords: Cord blood; Hematopoietic stem and progenitor cells; CD34+; Vitamin-C; Ascorbic acid; Expansion